"A boy, being a victim, nobody really buys that, you know?": Dynamics of sexual violence against boys. (August 2017) - Hohendorff, Jean Von; Habigzang, Luísa Fernanda; Koller, Silvia Helena
Abstract: The aim of this study was to present the dynamics of sexual violence against boys. Interviews were conducted with four male victims of sexual abuse between the ages of six and 10, as well as four psychologists employed in the health care system and involved in the treatment of sexually abused boys. Results were examined using thematic content analysis, based on six deductively identified themes corresponding to the following stages of sexual violence against children and adolescents: preparation, episodes, silencing, narratives, repression and overcoming. The results suggested that proximity between victims and offenders, who were mostly adolescent boys, was a facilitator of abuse. The interviews also revealed that victims faced significant levels of disbelief and discrimination. Lastly, the findings pointed to the importance of protective actions and of the system itself, though all practitioners perceived the latter as flawed and unprepared to handle cases involving sexually abused boys. These findings underscore the social invisibility of sexual violence against boys, due to the low number of referrals as well as the disbelief and discrimination, which permeates the management of these cases.